Playing games during pandemic, why not? The IDLE upon students’ efficacy and vocabulary - Muhammad Najmussaqib Diya Alhaq (Indonesian Journal of Applied Linguistics, 2022)
Advancements in the current era and challenges during the pandemic have given rise to an urgency for education practitioners and academicians to turn to informal learning outside the classroom. This is also the case with learners of English as a Foreign Language (EFL), who need to practise the language on an ongoing basis. For this purpose, they utilise the activity of digital gaming as a form of Informal Digital Learning of English (IDLE). This research examines the self-efficacy in learning English (as affective domain) and vocabulary mastery (as cognitive domain) of students with digital gaming experience within the IDLE framework. This sequential qualitative dominant mixed-method research involved 10 respondents out of 244 students with digital gaming experience. The data were collected by using a questionnaire, interview sessions, and receptive-productive vocabulary tests. The collected data were analysed according to Bandura’s Personal Agency (1989) and Raoofi’s (2012) study on self-efficacy, using descriptive statistics for vocabulary mastery, and Kallio et al.’s (2011) InSoGa model for measuring the degree of digital gaming. It was found that students with a medium and heavy degree of playtime or gaming experience had self-efficacy and good receptive-productive vocabulary mastery. The results also showed that efficacy degrees may vary, and students’ receptive test scores were always higher than or the same as their productive test scores. The findings showed IDLE-digital gaming could sustain in-class teaching through out-of-class learning. Thus, it implies that this research supports the IDLE-digital gaming application within an academic context.